Making Brittle Technologies Useful. (September 2017) - Rayo, Michael; Smith, Philip J.; Roth, Emilie; Sarter, Nadine; Mosier, Kathleen L.; Miller, Christopher A.
Across a wide variety of systems, from aviation and ground transportation to energy and financial systems, there continues to be a move toward introducing more powerful technological support. Research and practice have clearly demonstrated that, for these complex systems, human centered designs are critical, especially when anomalous scenarios arise. As a result, one important focus of research in cognitive systems engineering has dealt with understanding how brittle technologies influence joint cognitive system performance. This panel will address three issues: 1) What do we know about how system design affects human performance when the competence envelope for the incorporated technology is exceeded? 2) What guidance is available for the design of joint cognitive systems so that they are robust or resilient when these competence envelopes are exceeded? 3) What important research questions need to be addressed to further extend our understanding regarding how to design and integrate cognitive tools into the work environment and to translate this understanding into effective system designs.